Penguatan Pendidikan Karakter Religius Pasca Masa Pandemi Covid-19 Di Taman Pendidikan Al-Qur’an Addinul Islam Gambutus Pasca Masa Pandemi Covid-19 Di Taman Pendidikan Al-Qur’an (TPA) Addinul Islam Gambut - Karina, Luthfia Ayu; Fitria, Mia; Yuniarti, Setiafitrie; Marlina, Marlina; Aisah, Siti Nur (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to strengthen religious character education at the Addinul Islam Al-Qur'an Education Park, which previously stopped operating since the emergence of the Covid-19 pandemic which took place in early 2019 until 2022 and was reopened after the government began to establish a relaxation from the previous social life. This activity is carried out in the form of applying values which are the basis for religious cultivation, namely creating religious culture (religious character) which is vertical through activities to improve relationships with Allah SWT both in quality and quantity and which is horizontal, namely by creating good social relations. The final result of this activity is a form of support, provision and mentoring to optimize social, educational and religious activities as a way to strengthen students' awareness regarding the importance of religious character after the TPA is reopened. This is especially important for students because character education needs to be done from an early age as a basis for life skills which are very important for everyday life and in the future.